ANALISIS AKUNTABILITAS PENGELOLAAN ZAKAT BERDASARKAN SYARIAH ENTERPRISE THEORY PADA BAITUL MAL KOTA BANDA ACEH - Muchtamarini, Yulia; Jalaluddin, Jalaluddin (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This study aims to determine the accountability of zakat management in Baitul Mal Kota Banda Aceh according to Sharia Enterprise Theory (SET). This study uses a descriptive approach using interviews (questions) as a data collection tool. Respondents in this study were the finance head department of Baitul Mal Kota Banda Aceh. The results of the study show that: (1) In terms of accountability to Allah SWT is in accordance to SET, the opinion of the Baitul Mal Kota Banda Aceh supervisory board stated that they have done and run their duties according to the fatwa of the National Sharia Council; (2) The accountability to Direct stakeholders for donors / customers is in accordance to SET concept as seen from the disclosure of zakat fund reports which include the receipt of zakat funds obtained and distributed to parties in need through ZIS fund realization reports; (3) Horizontal accountability of direct stakeholders to employees is partly in accordance to SET, seen from the disclosure of policies on wages and remuneration to employees and extension workers. In terms of providing training and education to employees, Baitul Mal only provides training programs for extension workers; (4) Horizontal indirect stakeholders is in accordance to SET, as can be seen from the disclosure of information to the wider community in accessing zakat funds. However, not all information can be given openly, because there are some of the reports that become privacy; (5) The accountability to the environment is not accordance to SET, because Baitul Mal has never carried out programs related to the environmental preservation, because in this case Baitul Mal focuses on managing zakat funds intended directly to the community.